A Scoring and Grouping System of Climate Change Acceptance/Knowledge/Concern for Citizens in the United States, China and Vietnam - Coonen, Kayla; Cornett, Cora; Hammer, Ryan; Hermes, Hunter; Holmes, Austin; Nguyen, Tung; Pike, Ashley; Rauland, Anastasia; Wilson, Dylan; Jamelske, Eric M.; Boulter, James E.; Jang, Won Yong (My University, 2018)
With mounting scientific evidence regarding the realities of climate change including causes and consequences, the international/global importance of this issue cannot be overstated. Significant research has assessed public climate change views in developed countries including the United States and in the European Union. However, much less is known about public climate change views in developing countries. Surveys were conducted of American (4,927), Chinese (2,629) and Vietnamese (1,496) citizens in 2015-16 to provide comparisons of how citizens in developed/developing countries view climate change. We construct a scoring and group classification system based on responses to survey questions. This process yields an understandable metric for comparing acceptance/knowledge/concern of basic climate change realities across citizens in these three countries.
Color poster with text, images, charts, photographs, maps, tables, and graphs.
Keywords: Climate change – United States; Climate change – China; Climate change – Vietnam; Public opinion; Posters